COLLEGE STUDENTS’ PERCEPTIONS ON USING MOVIES FOR VOCABULARY LEARNING - Fauzi, Widia Rahmi; Muljanto, Setia (IPI Garut Press, 2021)
The purpose of the research was to found out college students’ perception on using movie as learning media for vocabulary learning. The participants of this research are 5 students four Grade at English Education Program in Garut. All participants are those who have taken general and academic course and have used movie media. In collecting the data, the researcher gave interviewed the sample that related to students’ perceptions. Data were collected by interview by using qualitative method. The result is analysis revealed that the students’ responses on using movie as learning media to learn vocabulary were positive, the researcher found 3 results. The first, learning media is very important. The second, students believe that the use of movies as a learning media have beneficial effect. The last, students agreed that movies are useful to learn some new words and improve their vocabulary learning even though they used Indonesian subtitles